2013
DOI: 10.1039/c3sm50237f
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed surface dynamics of poly(methyl methacrylate) chains in the corona of collapsed dry micelles tethered by a fluorinated block core

Abstract: The effect of chain constraint on the surface dynamic of poly(methyl methacrylate) (PMMA) was investigated in the context of polymer tethering to a micelle core. Film surfaces dominated by either poly(methyl methacrylate) (PMMA) tethered by a poly(2-perfluorooctylethyl methacrylate) (PFMA) micelle core or non-micellized free PMMA chains are fabricated by spin coating a solution of PMMA end-capped with various numbers of FMA units onto silica substrates. By measuring the surface rearrangement kinetics of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…Silicon (100) wafers (Aldrich Co.) were used as substrates, cut into 1.0 cm × 1.0 cm square chips, and then treated with a piranha solution (H 2 SO 4 :H 2 O 2 in a 3:1 v/v ratio) at 363 K for 30 min, as described in the literature. 42,43 The resulting native oxide covered silicon substrates (SiO 2 − −Si) were washed thoroughly with excessive de-ionized water and dried with nitrogen gas.…”
mentioning
confidence: 99%
“…Silicon (100) wafers (Aldrich Co.) were used as substrates, cut into 1.0 cm × 1.0 cm square chips, and then treated with a piranha solution (H 2 SO 4 :H 2 O 2 in a 3:1 v/v ratio) at 363 K for 30 min, as described in the literature. 42,43 The resulting native oxide covered silicon substrates (SiO 2 − −Si) were washed thoroughly with excessive de-ionized water and dried with nitrogen gas.…”
mentioning
confidence: 99%
“…Variations in surface structure of the micellar lms aer annealing treatment in air were evaluated by contact angle measurement as previously reported. 41,44 The micellar lms which had been heated in air at various temperatures were cooled to room temperature before contact angle measurement and SFG analysis. Contact angles (q) of water were measured by the sessile drop method at room temperature and ambient humidity with a Krüss DSA-10 contact angle goniometer (Hamburg, Germany).…”
Section: Characterizationmentioning
confidence: 99%
“…Accordingly, it is apparent that the aggregative structures of chains play an important role in the resultant surface chain dynamics. In our previous work, 41 the effect of the chain constraint on the surface dynamics of poly(methyl methacrylate) (PMMA) was investigated in the context of polymer tethering to a micelle core. It was observed that the onset temperature of rearrangement (T onset R ) and the activation barrier for relaxation (E a ) of surface PMMA chains in the corona increased linearly with increasing compactness of the micelle core.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] These enhanced surface dynamics of quasi-equilibrated homopolymer chains are very representative of the general behavior of macromolecular motions on a surface. However, it was reported previously 19 that chain aggregative structures signicantly inuence the surface dynamics of PMMA, in which the relaxation activation energy (E a ) and the onset temperature of surface rearrangement (T onset R ) of the micellized PMMA are much higher than those of the nonassociated free chains.…”
Section: Introductionmentioning
confidence: 97%